2003
DOI: 10.1080/1354850310001604577
|View full text |Cite
|
Sign up to set email alerts
|

Are exercise social-cognitive factors and behaviours different for adults with diabetes? A randomized community sample

Abstract: Exercise plays a key role in the prevention and delay of the onset of Type 2 diabetes and in the management of this disorder. To determine if there are differences in key social-cognitive determinants of exercise and self-reported physical activity levels between adults with diabetes and those without the condition, a random selected sample of adults was surveyed. A telephone interview assessed physical activity behaviour and key social-cognitive constructs from major health behaviour change theories/models. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Upon critical review, studies were excluded for the following result: participants were younger than 18 years of age; physical activity was not part of the study; and studies that examined interventions. This left 18 articles for this review [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] ; 16 studies were cross-sectional, [13][14][15][16][17][18][19][20][21][22]24,26,[28][29][30] and 3 were prospective. 23,25,27 Furthermore, 2 of the crosssectional studies used in-depth qualitative interview analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon critical review, studies were excluded for the following result: participants were younger than 18 years of age; physical activity was not part of the study; and studies that examined interventions. This left 18 articles for this review [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] ; 16 studies were cross-sectional, [13][14][15][16][17][18][19][20][21][22]24,26,[28][29][30] and 3 were prospective. 23,25,27 Furthermore, 2 of the crosssectional studies used in-depth qualitative interview analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Only 3 studies used the same activity measure: the Godin Leisure-Time Exercise Questionnaire. [25][26][27] Five studies reported the reliability and validity of their measurement tool, 14,18,22,25,26 and 9 studies failed to comment on the validity or reliability of their physical activity measurement. 13,15,17,[19][20][21][28][29][30] Poor weather (2) Ferrand et al 15 N/A Body image (þ) Social support (þ ) Glasgow et al 16 Education level (þ ) Perceived barriers (þ) N/A Disease status/severity (2) Perceived behavioral control (þ ) Grace et al 17 Age (þ ) Self-efficacy (þ) N/A Disease status/severity (2) Hays and Clark 18 Age (2) Perceived barriers (2) N/A Education level (þ ) Knowledge (0) Disease status/severity (2) Krug et al 19 Age (þ ) Perceived behavioral control (þ ) Social support (þ ) Lawton et al 20 Female gender (2) Perceived barriers (2) Availability of facilities (þ ) Disease status/severity (2)…”
Section: Physical Activity Ratesmentioning
confidence: 97%
See 1 more Smart Citation
“…Health factors were assessed using previously published self-report measures [33,34] to determine diabetes type, height and weight (used to calculate body mass index, BMI); daily use of insulin or oral antihyperglycemic medication.…”
Section: Methodsmentioning
confidence: 99%
“…This study however did not explore several other important psychosocial constructs from key socialcognitive models. The other study (Plotnikoff, Brez, & Brunet, 2003) was an exploratory investigation of a small sample of 46 adults with diabetes and 1550 adults without diabetes which examined key psychosocial constructs from major social-cognitive theories. Both of the above studies however did not discriminate between T1D and T2D, which is an important consideration given the different aetiology and pathology (Canadian Diabetes Association Clinical Practice Guidelines Expert Committee, 2003) and physical activity levels (Plotnikoff et al, 2006) between these two diabetes groups.…”
Section: Introductionmentioning
confidence: 99%